TRIBAL PEOPLE AND ISSUES OF ACCESS TO LAND - Brahma, Ashok; Mushahary, Jhanin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Issues of access to land for tribal people in the Bodoland Territorial Region have historically been a significant concern. The region has faced challenges related to land rights and conflicts over land ownership between tribal communities and non-tribal settlers, leading to tensions and sporadic violence. The present objectives of study are to investigate the historical land rights of the tribal people to understand their connection to the land and examine conflict related to land access. The study covers the three tribal groups in the four districts of the Bodoland Territorial Region of Assam, through the primary and secondary sources of data. The findings reflect the right-to-land, land disputes, and land conflicts over land ownership and rights often lead to displacement and insecurity, exacerbating their vulnerability. Limited access to land and resource production due to historical marginalisation and insufficient legal recognition of tribal land rights hinders their ancestral land ties and economic development. Efforts to address these issues by ensuring secure land rights through legal documentation to protect their lands from encroachment and displacement. It requires involving tribal people in decision-making processes on land rights and use, historical land maintenance, empowering tribal communities through capacity-building, education, advocating for policies, and fair distribution of land resources.